Santripreneur Penghasil Kerajinan dari Limbah Plastik di Kawasan Pondok Pesantren KH. Murodi Mranggen Demak - Muhdi Muhdi; Sunan Baedowi; Achmad Buchori; Mahmud Yunus (Journal of Dedicators Community, 2021)
The amount of plastic waste around the Mranggen Market and Pondok Pesantren K.H. Murodi Mranggen Demak is a cause for concern. Good waste management so that plastic waste has use value and is beneficial for the environment around Islamic boarding schools is the goal in this service. The methods used are: problem mapping, design, manufacture, operation test, operation assistance and marketing training for production products. The strategy used to make plastic waste valuable is by conducting training in making variations of plastic waste product crafts with Eco-Bricks made into chairs, flower vases, bags, wallets, prayer mats and others. In addition, it is to strengthen good waste management among students. The results of this santripreneur activity are 1) Santri feel excited to understand and do entrepreneurship/studentpreneurs from an early age; 2) students understand the importance of processing waste and the importance of providing added value to products made from plastic waste, 3) 80 percent of students are able to make variations of crafts from plastic waste and 20 percent still need further assistance, 4) marketing is carried out in collaboration with MSMEs in Indonesia. Semarang and Demak so that it can make passive income for students.